1999
DOI: 10.1101/lm.6.5.500
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gene Expression During REM Sleep Depends on Prior Waking Experience

Abstract: In most mammalian species studied, two distinct and successive phases of sleep, slow wave (SW), and rapid eye movement (REM), can be recognized on the basis of their EEG profiles and associated behaviors. Both phases have been implicated in the offline sensorimotor processing of daytime events, but the molecular mechanisms remain elusive. We studied brain expression of the plasticity-associated immediate-early gene (IEG) zif-268 during SW and REM sleep in rats exposed to rich sensorimotor experience in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
161
3
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(196 citation statements)
references
References 60 publications
23
161
3
9
Order By: Relevance
“…Whereas non-REM sleep is characterized by diminished activity of such genes and a greatly reduced ability to induce synaptic long-term potentiation, REM sleep provides a more adequate milieu of neurotransmitters and modulators for synaptic plastic changes (Ribeiro and Nicolelis, 2004;Bramham and Srebro, 1989). Ribeiro et al (Ribeiro et al, 1999 revealed an increased expression of the immediate early genes arc and zif-268 during REM sleep after induction of long-term potentiation during prior wakefulness. Importantly, regulation of plasticity-related early genes depends strongly on the cholinergic receptor activation (von der Kammer et al, 1998(von der Kammer et al, , 2001Teber et al, 2004) and, here, blocking these receptors interfered likely with transcriptional changes required for long-term memory storage.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas non-REM sleep is characterized by diminished activity of such genes and a greatly reduced ability to induce synaptic long-term potentiation, REM sleep provides a more adequate milieu of neurotransmitters and modulators for synaptic plastic changes (Ribeiro and Nicolelis, 2004;Bramham and Srebro, 1989). Ribeiro et al (Ribeiro et al, 1999 revealed an increased expression of the immediate early genes arc and zif-268 during REM sleep after induction of long-term potentiation during prior wakefulness. Importantly, regulation of plasticity-related early genes depends strongly on the cholinergic receptor activation (von der Kammer et al, 1998(von der Kammer et al, , 2001Teber et al, 2004) and, here, blocking these receptors interfered likely with transcriptional changes required for long-term memory storage.…”
Section: Discussionmentioning
confidence: 99%
“…We found a time window during SWS Ïł2 h after the rat learned the odorreward contingency when the noradrenergic neurons of the locus ceruleus, which are usually quiescent during SWS, show a surge of activity that is never seen in animals that have not been in the learning situation (Sara et al, 2005). Learning-related delayed release of noradrenaline in forebrain neurons (Tronel et al, 2004), which are potentially engaged in reactivation during sleep, would serve as an effective signal or "molecular switch" for gene expression during a subsequent REM episode (Ribeiro et al, 1999;Cirelli and Tononi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…14 Ribeiro and colleagues found that the exposure to a new environment for 3 hours 15 results in the immediate cortical and hippocampal induction, during waking, of plasticity-related gene zif-268, 16 followed by its downregulation during NREM sleep, and then again by its increased expression during REM sleep (relative to NREM sleep). Intriguingly ~ 3 min of NREM sleep were enough to downregulate waking-induced zif-268 expression, and ~ 2 min of REM sleep were sufficient to detect its selective reinduction, even if both NREM and REM rats were awake during the last 30 min before sacrifice.…”
Section: Sleep Is Present and Homeostatically Regu-lated In All Animamentioning
confidence: 99%